2009
DOI: 10.1002/jcp.21934
|View full text |Cite
|
Sign up to set email alerts
|

Calcium‐stimulated mitogen‐activated protein kinase activation elicits Bcl‐xL downregulation and Bak upregulation in notexin‐treated human neuroblastoma SK‐N‐SH cells

Abstract: Notechis scutatus scutatus notexin induced apoptotic death of SK-N-SH cells accompanied with downregulation of Bcl-xL, upregulation of Bak, mitochondrial depolarization, and ROS generation. Upon exposure to notexin, Ca(2+)-mediated JNK and p38 MAPK activation were observed in SK-N-SH cells. Production of ROS was a downstream event followed by Ca(2+)-mediated mitochondrial alteration. Notexin-induced cell death, mitochondrial depolarization, and ROS generation were suppressed by SB202190 (p38 MAPK inhibitor) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…Measurement of caspase-3/-8/-9 activity, detection of apoptotic cells using annexin V/propidium iodide staining and Western blot analyses were performed in essentially the same manner as previously described (Liu and Chang, 2009;Chen et al, 2010;Chen and Chang, 2014).…”
Section: Other Testsmentioning
confidence: 99%
See 1 more Smart Citation
“…Measurement of caspase-3/-8/-9 activity, detection of apoptotic cells using annexin V/propidium iodide staining and Western blot analyses were performed in essentially the same manner as previously described (Liu and Chang, 2009;Chen et al, 2010;Chen and Chang, 2014).…”
Section: Other Testsmentioning
confidence: 99%
“…Following induction of apoptosis, cytosolic and pellet (mitochondrial) fractions were generated using a digitonin-based subcellular fractionation technique according to the method described in Chen et al (2010). Cytochrome c and BAX were detected by Western blot analysis.…”
Section: Separation Of Cytosolic and Mitochondrial Fractionsmentioning
confidence: 99%
“…It has been widely accepted that a higher Bax/Bcl‐2 ratio alters mitochondrial permeability and ΔΨm to activate caspase‐3, which, in turn, induces apoptosis. Several studies have suggested that JNK and p38 may be the upstream signals of the Bax/Bcl‐2‐evoked mitochondrial apoptosis pathway (Kang and Lee,2008 ; Su et al,2009; Chen et al,2010b ; Deng et al,2010). Our previous study showed that Bax/Bcl‐2 ratio elevation and caspase‐3 activation were both detected synchronously with apoptosis in TBT‐treated human amnion cells (Zhu et al,2007).…”
Section: Introductionmentioning
confidence: 99%
“…Apoptosis ATF2/CREB1 heterodimer binds to the CRE element of the BCL2 promoter . ATF2 induces BAK upregulation (Chen et al, 2010). MAP3K5 (ASK1) activates ATF2 and FADD-CASP8-BID signalling, resulting in the translocation of BAX and BAK, and subsequently mitochondrial dysregulation (Hassan et al, 2009).…”
Section: Histones Chromatinmentioning
confidence: 99%